Attack on Titan. Before the fall. 6 - Isayama, Hajime, 1986- (Kodansha, 2014)
"Cut alive from his mother's womb afer she had been eaten by a rampaging Titan, Kuklo has spent his entire life in chains as a freakish curiosity and a feared abomination. Eventually the boy they call the "Titan's son" finds hemself sold to wealthy merchant Dario Inocencio as a plaything for his cruel and ambitious son Xavi. Kuklo knows nothing but abuse and neglect but help may come from the most unexpected place"--Page 4 of cover.